Intramural hematoma or aortic dissection – a diagnostic and therapeutic problem. A case report - Suder, Bogdan; Wasilewski, Grzegorz; Bartuś, Krzysztof; Sadowski, Jerzy; Kapelak, Bogusław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
The authors present a case report of a 60-year-old patient with an ascending aortic aneurysm along with the associated diagnostic and therapeutic problems. The choice of therapy in patients with aortic intramural hematoma is difficult and should be based on comprehensive evaluation of the patient’s status as well as on the experience of the radiologist and surgeon.